Restoration of the Selo Gending Lumajang Site Following the Religious Dualist Controversy - Nurhafid Ishari; Taqwa Nur Ibad; Muhammad Farid (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The A traditional heritage site called Selogending Kandangan is situated in Krajan Hamlet, Kandangan Village, and Senduro District. While having immense potential, the Selogending Kandangan property is currently in terrible condition and unsuitable for domestic and international tourism use. A traditional village ritual known as the Unan-unan village activity, which is performed annually as well as every Hindu year or, to put it more simply, once every five years in the Christian calendar, is performed at the Selogending Kandangan location.The people of Kandangan did not realize this condition, so the Pokdarwis and Karang Taruna through our assistance tried to revive the cultural heritage of the Selogending Kandangan site. The initial step taken by Pokdarwis and Karang Taruna was to form an organizational structure which has not been working so far. The organizational structure has actually been formed several years ago, but there is no work application. Overall, the program implemented by the Pokdarwis and Karang Taruna was carried out according to plan, even though there were internal and external obstacles. The organizational structure that has been formed will propose to the village meeting that the selogending stable site is planned for next year.